2009
DOI: 10.1248/yakushi.129.759
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Analysis and Clinical Efficacy of Kampo Medicine, Maoto, Extract Suppository Against Pediatric Febrile Symptoms

Abstract: A traditional Chinese herbal medicine, Kampo medicine, maoto, has been widely used in the treatment of febrile symptoms caused by viral infection. This herbal extract granule for oral use, however, is not well accepted by infants or young children due to its unpleasant taste and odor. Therefore, we prepared Kampo medicine, maoto, suppository and investigated the pharmaceutical and clinical e‹cacy of the suppository. Kampo medicine, maoto, granules were micropulverized and homogeneously dispersed into Hosco-H15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Antipyretic potency of Maoto (Ma-huang-tang in Chinese) in human [8, 22] and Gingyosan (Yin-qiao-san in Chinese) in mice [23, 24] have been reported, Kakkonto (Ge-gen-tang in Chinese) has increased IL-12 production in the BALF of mice [25], and Shoseiryuto (Xiao-qing-long-tang in Chinese) has augmented anti-influenza virus IgA antibody followed by alleviation of the proliferation of influenza virus in the respiratory tract of mice [26–28]. Based on Kampo medicine theory, these formulas have been used in early phase of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Antipyretic potency of Maoto (Ma-huang-tang in Chinese) in human [8, 22] and Gingyosan (Yin-qiao-san in Chinese) in mice [23, 24] have been reported, Kakkonto (Ge-gen-tang in Chinese) has increased IL-12 production in the BALF of mice [25], and Shoseiryuto (Xiao-qing-long-tang in Chinese) has augmented anti-influenza virus IgA antibody followed by alleviation of the proliferation of influenza virus in the respiratory tract of mice [26–28]. Based on Kampo medicine theory, these formulas have been used in early phase of infection.…”
Section: Discussionmentioning
confidence: 99%
“…11) One milliliter of p-hydroxy propylbenzoic acid MeOH solution (IS solution, 0.7 mg/mL) was added to the solution. Then, the resultant solution was centrifuged (3500 rpm, 5 min).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Kampo medicine maouto suppository is evaluated using l-ephedrine as an indicative substance. 11) In this study, we investigated the effects of the size of powdered goreisan on the content uniformity and dissolution behavior of goreisan suppositories by using the detection of CA. Then, the pharmacokinetics of CA after administration of the goreisan suppository and goreisan enema in rabbits was investigated to obtain fundamental basic information on its clinical efficacy.…”
mentioning
confidence: 99%
“…Ma-huang-tang has been widely used in China to manage influenza diagnoses among children. Without exhibiting adverse effects, it has been validated to be clinically useful in neonates, infants, and children with febrile viral symptoms (Nishimura et al, 2009). Additionally, it has been shown that it might potentially be useful in patients aged ≤5 who have a low sensitivity to oseltamivir and experience problems when using zanamivir (Toriumi et al, 2012).…”
Section: Use Of Tcm In Treating Influenza Among Children and During Pmentioning
confidence: 99%